Digital Transformation in Islamic Religious Education: A Systematic Literature Review of Scopus-Indexed Publications (2010–2025) - Ka'anto Ka'anto (STKIP Al Islam Tunas Bangsa dan HEPI, 2026)
This study aims to systematically analyze the development of research on digital transformation in Islamic Religious Education (IRE) indexed in Scopus during the 2010–2025 period. The focus of the study includes publication trends, main themes, types of technologies implemented, challenges faced, and future research directions. This study employs the Systematic Literature Review (SLR) method by adopting the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Literature searches were conducted in the Scopus database using relevant keywords, yielding 312 initial articles. After undergoing screening and eligibility processes, 47 articles that met the inclusion criteria were obtained for in-depth analysis. The analysis results show a significant increase in publications on digital transformation in IRE in the last five years, especially post-COVID-19 pandemic. The main themes identified include: (1) integration of e-learning and mobile learning in IRE instruction, (2) development of digital-based learning media for Quranic education, (3) utilization of learning management systems (LMS) in Islamic educational institutions, (4) digital competence of IRE educators, and (5) ethical challenges in the digitalization of Islamic values. Indonesia and Malaysia are the largest contributors to publications in this field. Research gaps are still found in the aspects of artificial intelligence (AI) integration, long-term impact evaluation, and cross-cultural exploration. This study provides a comprehensive map of the research landscape on digital transformation in IRE, which can serve as a foundation for policy development, pedagogical innovation, and future research agendas. This review is the first SLR that specifically captures digital transformation in IRE with a 15-year time span (2010–2025) based on Scopus data, employing a rigorous PRISMA protocol, and presenting a comprehensive thematic synthesis.